PENGARUH PENGETAHUAN LINGKUNGAN DAN SIKAP KONSUMEN TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN (Studi pada Konsumen Air Mineral ADES di Kota Klaten) - Kussudyarsana Kussudyarsana; Nur Yuliana Devi (Jurnal Fokus Manajemen Bisnis, 2020)
Business competition in the development in the era of globalization and high environmental damage requires companies to be able to meet the needs of consumers but also protect the preservation of the environment. This research is a quantitative causal research that allows to know the relationship that is influential between two or more variables by using two hypothesis tests, simple regression analysis and multiple linear regression analysis. The population in this study is Ades mineral water consumers who live in the city of Klaten, while the study sample was 125 respondents with a non-probability sampling purposive sampling method as a sampling method. Based on the results of research that environmental knowledge has a significant effect on consumer attitudes, environmental knowledge has no significant effect on purchase intention, consumer attitudes positively influence purchase intention. The attitude of consumers is also a variable that mediates the influence of environmental knowledge on purchase intention, the results of this study indicate that consumer attitudes do not mediate between independent and dependent variables. In this study the mediating variable is a fulling mediation model because a to Z has a significant effect, b to Y has a significant effect, and X to Y has no significant influence.